OVERVIEW OF THE CHARACTERISTICS AND USE OF DRUGS FOR SEXUALLY TRANSMITTED INFECTION (STI) PATIENTS DURING THE COVID-19 PANDEMIC 2020 - 2021 AT RSUD ABDUL WAHAB SJAHRANIE SAMARINDA - Taris Amazida Zatayumni; Achmad Kadri Ansyori; Fitri Handayani (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
During the COVID-19 pandemic, many infectious diseases other than COVID-19 are often neglected in their spread. One of the most common infectious diseases is Sexually Transmitted Infections (STI). STIs are reproductive tract infections caused by bacteria, viruses, and parasites, most of which are transmitted through sexual contact. The high incidence of STIs shows that the public's knowledge of STIs is still low. This study aims to determine the use of drugs and the characteristics of STI patients during the COVID-19 pandemic in 2020-2021 at RSUD Abdul Wahab Sjahranie Samarinda. This research is non-experimental. The research method used is descriptive quantitative, which is done retrospectively. The results showed a decrease and increase in the number of patients during the COVID-19 pandemic. The total number of STI patients in this study was 48 patients, consisting of 17 patients in 2020 and increasing to 31 patients in 2021. The most characteristics of STI patients during 2020-2021 are male patients, the majority of STI patients aged 17-25 years, high school education level, working as private employees, and unmarried. The most common types of STIs in 2020 were gonorrhea and syphilis in 2021. The most frequently used drug for the treatment of syphilis was the injection of benzathine penicillin, for the treatment of gonorrhea was azithromycin, for the treatment of condyloma acuminata was cefixime and for the treatment of genital herpes was acyclovir.